Pests of cassava in the world - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1972)
About 150 pests of cassava are cited. About 110 are insects and the rest are nematodes (38), arachnids (3) and chilopods (1). Insects are listed by orders; the stage causing damage, type of damage, and distribution are listed as well. (CIAT)